2013
DOI: 10.1177/1534484313494088
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HRD in Stimulating, Supporting, and Sustaining Creativity and Innovation

Abstract: Challenging environments call for creativity and innovation, dynamic processes that depend upon the interaction of the individual with the social and organizational environment, placing people issues in the foreground. Extant literature suggests a number of problems. First, the frequent confusion that surrounds what this actually means in practice. Second, regardless of the potential for all creative idea generation is not common for most individuals. Finally, successful exploitation of new ideas must overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 110 publications
(206 reference statements)
0
37
0
1
Order By: Relevance
“…• An alternative interpretation considers that CPS training might increase openness (Loewenberger, 2013). Both interpretations have implications for HRD in valuing membership of professional associations, conference attendance and networking in increasing the pools of knowledge and experience.…”
Section: Determinants Of Creativity Identified By Extant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…• An alternative interpretation considers that CPS training might increase openness (Loewenberger, 2013). Both interpretations have implications for HRD in valuing membership of professional associations, conference attendance and networking in increasing the pools of knowledge and experience.…”
Section: Determinants Of Creativity Identified By Extant Literaturementioning
confidence: 99%
“…Given the significance of learning and culture change to the promotion of creativity and innovation, synthesis with HRD (Loewenberger, 2013) remains limited in comparison to general support for HRM and leadership. A focus on the dynamic interaction between individual development of creative thinking skills and a supportive climate remains rare.…”
Section: Hrd Implications For Sustainable Creativity Innovation and mentioning
confidence: 99%
See 1 more Smart Citation
“…The objective is to validate the hypotheses of this theory to help executives and decision makers in Saudi architectural firms to enhance their understanding of what makes their employees, and specifically designers, more creative and their organizations more innovative. approach (Chambers, 1969;Haberland & Dacin, 1992;Borghini, 2005;Hee Kim, 2006;Kurtzberg, 2005;Hansen, Lumpkin, & Hills, 2011;Massaro, Bardy, & Pitts, 2012;Loewenberger, 2013). Many researchers have examined the factors that affect organizational creativity but Amabile's "Componential Model of Organizational Creativity" remains the most popular and widely used (Coveney, 2008;Tseng & Liu, , 2011;Castro, Gomes, & de Sousa, 2012;Stuhlfaut & Windels, 2012;Yeh-Yun Lin & Liu, 2012;Yi, Hu, Plucker, & McWilliams, 2013;Perry-Smith, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, challenging work through supportive supervision has been proven to enhance employees' intrinsic motivation and thus led to more positive and creative outcomes (Haas, 2006;Zhou et al, 2012). Loewenberger (2013) found that creativity-supporting work environments are more likely to introduce new ideas and products.…”
Section:  Challenging Workmentioning
confidence: 99%